PENGARUH DIKLAT DAN DISIPLIN KERJA GURU TERHADAP KINERJA GURU AGAMA PADA MADRASAH IBTIDAIYAH DI KOTA TANGERANG SELATAN - Neneng LM (Jurnal Dialog, 2016)
This study aims to determine the factors that affect the performance of religious teachers in Islamic Elementary School in South Tangerang City. The study employed causal survey method with the population of 85 religious teachers in Islamic Elementary School in South Tangerang City. Given that the sample is less than 100 participants, the respondents in this study is the total sample (the whole population). Data were collected using a questionnaire to measure the variables of teacher performance, education and training, and work discipline. The coefficient of reliability (alpha value) is consecutively 0.8074; 0.7126. The results indicate that, first, there is a direct and significant effect of education and training to the teacher performance, indicated by the value þ = 1.030 with a regression equation Y = 28.529 + 1,030X1, r1y correlation coefficient = 0.917, and the coefficient of determination R square = 0.841, or 84,1%. Second, there is a positive and significant impact of education and training on work discipline, shown by the p-value = 0.00 <0.05 with a regression equation X2 = 6.214 + 0,733X2, correlation coefficient (R2.1) = 0.928 and F count = 516.609, and the R Square = 0.862, or 86.2%. Third, there is a direct and significant effect of performance to work discipline, which is indicated by the value þ = 0.839, the regression equation Y = 32.015 + 0,839X2. Fourth, there is a direct influence of the training and work discipline on the teacher performance, the regression equation Y = 30.070 + 0,313X1 + 0,610X2, Ry.12 correlation coefficient = 0.952, and the R square = 0.907 or 90.7%. The findings imply that the religious teacher performance in Islamic Elementary School in South Tangerang City can be improved by participating education and training program and improving work discipline. KEYWORDS: Training, work discipline, religious teacher performance, public elementary school